Cationic Amino Acid Transporter-1-Mediated Arginine Uptake Is Essential for Chronic Lymphocytic Leukemia Cell Proliferation and Viability - Werner, Anke; Pieh, Daniel; Echchannaoui, Hakim; Rupp, Johanna; Rajalingam, Krishnaraj; Theobald, Matthias; Closs, Ellen I.; Munder, Markus (Frontiers in Oncology, 2019)
Interfering with tumor metabolism by specifically restricting the availability of extracellular nutrients is a rapidly emerging field of cancer research. A variety of tumor entities depend on the uptake of the amino acid arginine since they have lost the ability to synthesize it endogenously, that is they do not express the rate limiting enzyme for arginine synthesis, argininosuccinate synthase (ASS). Arginine transport through the plasma membrane of mammalian cells is mediated by eight different transporters that belong to two solute carrier (SLC) families. In the present study we found that the proliferation of primary as well as immortalized chronic lymphocytic leukemia (CLL) cells depends on the availability of extracellular arginine and that primary CLL cells do not express ASS and are therefore arginine-auxotrophic. The cationic amino acid transporter-1 (CAT-1) was the only arginine importer expressed in CLL cells. Lentiviral-mediated downregulation of the CAT-1 transporter in HG3 CLL cells significantly reduced arginine uptake, abolished cell proliferation and impaired cell viability. In a murine CLL xenograft model, tumor growth was significantly suppressed upon induced downregulation of CAT-1 in the CLL cells. Our results suggest that inhibition of CAT-1 is a promising new therapeutic approach for CLL.